2-Fluorophenol degradation by aerobic granular sludge in a sequencing batch reactor - Duque, Anouk F. (2012)
Aerobic granular sludge is extremely promising for the treatment of effluents containing toxic compounds, and it can economically compete with conventional activated sludge systems. A laboratory scale granular sequencing batch reactor (SBR) was established and operated during 444 days for the treatment of an aqueous stream containing a toxic compound, 2-fluorophenol (2-FP), in successive phases. Initially during ca. 3 months, the SBR was intermittently fed with 0.22 mM of 2-FP added to an acetate containing medium. No biodegradation of the target compound was observed. Bioaugmentation with a specialized bacterial strain able to degrade 2-FP was subsequently performed. The reactor was thereafter continuously fed with 0.22 and 0.44 mM of 2-FP and with 5.9 mM of acetate (used as co-substrate), for 15 months. Full degradation of the compound was reached with a stoichiometric fluoride release. The 2-FP degrading strain was successfully retained by aerobic granules, as shown through the recovering of the strain from the granular sludge at the end of the experiment. Overall, the granular SBR has shown to be robust, exhibiting a high performance after bioaugmentation with the 2-FP degrading strain. This study corroborates the fact that bioaugmentation is often needed in cases where biodegradation of highly recalcitrant compounds is targeted.